Assessment of periodontal disease severity in patients with cardiovascular disease: A cross-sectional study - Amita Rao; K Subramanyam; Ballamoole Krishna Kumar; Neevan D'Souza (Wolters Kluwer Medknow Publications, 2022)
Background: Periodontitis is a biofilm-induced chronic inflammatory disease that affects the tooth-supporting structures. Transient bacteremia during periodontal infection may lead to direct bacterial invasion of endothelial cells. Aim: To observe if the patient's periodontal status has an influence on the severity of the cardiac disease. Materials and Methods: Subgingival and atherosclerotic plaques were extracted from patients with coronary artery disease in this cross-sectional analytical study. Based on the nested polymerase chain reaction results, 44 patients were age- and gender-matched and divided into two groups based on the presence or absence of periodontal pathogens belonging to the red complex in the atherosclerotic plaque samples. Version 20.0 of IBM SPSS Statistics for the Windows was used to analyze the data. The Pearson Chi-square test was done to investigate the association between periodontal status and pathogen detection, as well as determine the relationship between periodontal severity and cardiac severity. P < 0.05 was considered to be statistically significant. Results: Statistically insignificant association was observed between periodontal severity and the detection of the periodontal pathogens Porphyromonas gingivalis and Tannerella forsythia in the subgingival and atherosclerotic plaques in Group A; however, a significant association was observed for the pathogen Treponema denticola in the subgingival plaque for both Groups A (P = 0.039) and B (P = 0.005). No significant association was observed between the periodontal severity and cardiac severity for Groups A (P = 0.40) and B (P = 0.277). A weak positive but statistically insignificant (P = 0.097) correlation was observed for overall periodontal and cardiac severity. Conclusion: A higher percentage of patients had generalized chronic periodontitis in the group that tested positive for the pathogens in the atherosclerotic plaques, indicating a possible influence of periodontal status on cardiac outcomes.